(untitled) (Altre Modernità, 2019)
Scientist Ignacio Domeyko’s 1845 trip to the Chilean Araucanian region was taken in the context of his desire to visit Chile a bit more before his return to Poland: see the country of the Araucanian savages. This visit would give birth to a unique book that constitutes a true defense of the Araucanians’ human rights: Araucania and its inhabitants. Domeyko, who was highly respected in Chile, strongly influenced the establishment of a new view of the indigenous inhabitants living in the south of the country. His study has originated numerous revisions and critical articles. In this work I review Domeyko’s human rights view of the Araucanian woman he gleans through his coexistence with them. His narrative occurs when he had already been living in Chile for twenty two years, and is not separate from the overriding ideology during that century, nor from the historical facts of the civilizing projects and Chilean progressivism; rather, it is centered in the project. The positive characteristics of the native are mitigated when noting some of those Domeyko considers serious faults, such as the authoritarianism of the man over the woman; the treatment and mistreatment of her; her confinement and impossibility of self-liberation. German traveler and mines engineer Paul Tretler arrives in the Araucanian region fourteen years later in 1859 and not only notices what Domeyko had observed in 1845 about the state of the Araucanian woman, but also gets close to some of them; he witnessed trials against Araucanian women; he also accepted/received the confession and request for help of a pregnant white woman prisoner, wife of one of the caciques, and victim of the other wives. Two of his books are included in this paper: Andanzas de un alemán en Chile 1851-1863 and La provincia de Valdivia y los Araucanos.